Correlation Between International Regulations and Domestic Regulations in the Field of Human Rights and Freedoms (Journal of Legal Studies, 2024)
The correlation between international regulations and domestic regulations in the field of human rights and freedoms" analyses the relationship and mutual impact between international human rights norms and standards and the domestic legislation of the States. The paper investigates the importance and ways in which international regulations influence and are implemented in the domestic legislation of States to ensure the protection and observance of human rights. First of all, States have to pass appropriate domestic legislation to implement and give practical effect to international human rights norms and standards. This means that domestic regulations must be consistent with States' international obligations and ensure the protection and respect of human rights at a national level. Secondly, international human rights regulations can serve as instruments for interpreting and applying domestic law. States can use international standards as references for interpreting and applying their domestic laws, thereby ensuring that human rights are duly observed and protected.